Puberty and NeuroDevelopment in adolescents (PANDA): a study protocol - Katherine O. Bray; Olivia Durbin; Stephanie Hartanto; Muskan Khetan; Daniel Liontos; Sarah J. Manuele; Isabel Zwaan; Despina Ganella; Megan M. Herting; Jee Hyun Kim; Michele O’Connell; Elena Pozzi; et al. (BMC Pediatrics)
Abstract Background Biopsychosocial changes during adolescence are thought to confer risk for emotion dysregulation, and in particular, anxiety disorders. However, there are substantial gaps in our knowledge about the biological mechanisms underlying anxiety during adolescence, and whether this contributes to the higher prevalence in females. The Puberty and NeuroDevelopment in Adolescents (PANDA) study aims to examine links between biological (sex hormones, cortisol) and social environmental factors and brain function during adolescence, with a focus on key processes (emotion regulation, fear learning) identified as relevant for the development of anxiety disorders. Methods PANDA is a cross-sectional study with an observational design that aims to recruit a total of 175 adolescents aged 11-16 (majority female) and their parents/guardians, from the community. Brain function will be examined using magnetic resonance imaging (MRI), including functional MRI tasks of emotion regulation and fear learning. Hormones will be measured from hair (i.e., cortisol) and weekly saliva samples (i.e., oestradiol, progesterone, five across a month in females). Questionnaires and semi-structured interviews will be used to assess mental health and social environmental factors such as parenting and adverse childhood experiences. An online study of 113 adolescents was also incorporated during the COVID-19 pandemic as a questionnaire-only sub-study. Discussion Strengths of this study include the collection of multiple saliva samples to assess variability in hormone levels, examination of the timing of adverse childhood experiences, inclusion of both maternal and paternal parental factors, exploration of mechanisms through the examination of brain structure and function, and multi-method, multi-informant collection of mental health symptoms. This study addresses important gaps in the literature and will enhance knowledge of the biological and environmental contributors to emotion dysregulation and anxiety in adolescents.